Manajemen Strategi Badan Usaha Milik Desa (BUM Desa) dalam Meningkatkan Pendapatan Asli Desa (Studi Kasus pada Wisata Cafe Sawah Desa Pujon Kidul, Kecamatan Pujon, Kabupaten Malang) - Weristi, Selvy; Hayat; Wulan Sekarsari, Retno (Idarotuna : Journal of Administrative Science, 2025)
The establishment of Cafe Sawah Pujon Kidul has a good effect on village income, particularly village original income, which is what spurred this study. The goal of this study is to determine the type of management strategy that Cafe Sawah Pujon Kidul's managers employ. The administrators of BUM Pujon Kidul Village and the managers of Cafe Sawah served as the study's subjects. The management strategy used at Cafe Sawah Pujon Kidul to boost village original income is the next focus of this study. This kind of study uses a qualitative, descriptive methodology. The Sawah Cafe Manager, the Village Head, the Chair of the Village BUM, as well as Supervisors, Marketing, and Employees, made up the ten (10) research informants. Observation, interviews, and documentation were used to gather data, and qualitative descriptive techniques were used to analyze the findings. According to this study, Cafe Sawah's management strategy has not been properly implemented throughout. But in general, a number of management functions have been put into practice. There are still a lot of chances for Cafe Sawah Pujon Kidul to grow and advance because of its potential. despite the fact that there are still a number of obstacles to overcome.